A Comparative Study in Psychological Burning among Football Referees And Football Referees of First Class Halls in Southern Zone in Iraq - Ahmed Sa’ad Abdul Razak 1 , Ali Hussein Ali 1, Anmar Atshan Khargan2 , Asmaa Sattar Khudhair2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The research aimed to know about differences in the phenomenon of psychological burning among football referees and football referees of first class halls in southern zone. The researchers assumed that there are differences with moral guidance in the phenomenon of psychological burning among football referees and football referees of first class halls in southern zone. The researchers had mentioned to the theoretical studies that contained of multiple researches related to the topic of the research. The researchers used the describing method by principle of comparative studies due to is suitable for the problem of the research, The research sample was contained from (28) referees divided onto (14) football referees and (14) referees of first class halls after implementing measure of psychological burning on a sample of research the researchers did to find differences between the two groups by using the law of ( T ) for the independent samples , After that theses results has been previewed and analysis and discussed so the researchers reached to conclusions the most important of the is that there are no any moral differences between the groups of football referees and football referees of first class halls in southern zone.